AN EVALUATION OF TURKEY'S FIT TO BRICS PROFILE IN TERMS OF ENVIRONMENTAL PERFORMANCE, SUSTAINABLE DEVELOPMENT GOALS AND INCOME LEVEL (Third Sector Social Economic Review, 2024)
The Sustainable Development Goals Index (SDGI), which assesses the current status of countries in achieving global sustainable development goals, and the Environmental Performance Index (EPI), which measures the environmental sustainability performance of countries as a whole, are considered essential parameters in terms of providing an idea about the level of development of nations. While the SDGs are based on 17 interlinked global goals targeted to be achieved by the United Nations by 2030, the EPI is based on 32 performance indicators in 11 topic categories covering environmental health and ecosystem vitality. This study aims to examine the relationship between Gross National Product (GNP), EPI, and SDGI scores of BRICS-T countries for 2020 and their status among 155 countries and to examine whether Turkey is a country that can represent BRICS countries well in terms of environmental performance, sustainable development goals, and income in terms of regional unions. The K-means method was applied to cluster the countries in the study. The number of clusters was decided by the Elbow method. When the analysis results are analyzed, it is observed that BRICS-T countries perform below the overall average of EPI while they perform above the general standard of SDGI. On the other hand, it is found that Turkey's EPI score is the closest to the BRICS-T average, while its SDGI performance is below the BRICS-T average.
Keywords: Sustainable Development; Environmental Performance; Cluster Analysis; Gross National Product; BRICS-T